A proposed constructivism-based instructional model to enhance metacognition and mathematical problem-solving skills in Bhutanese grade nine students - Subba, Bijoy Hangmo; Chanunan, Skonchai; Poonpaiboonpipat, Wanintorn (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
The enhancement of metacognitive abilities and problem-solving skills is essential for effective mathematics instruction. However, these critical components are frequently overlooked in traditional teaching practices. This study addresses the challenges and requirements faced by mathematics educators and explores the integration of constructivist activities in classroom settings. It aims to develop and evaluate the suitability of an instructional model designed to address these issues. Employing a mixed-method approach within a research and development framework, the study gathered data through semi-structured interviews with seven mathematics teachers in Bhutan to identify their instructional challenges. Additionally, two experts from Bhutan and one from Thailand were consulted to provide insights into constructivist teaching methodologies. The content analysis of teacher interviews revealed a predominant reliance on structured, teacher-centered instructional methods, with limited emphasis on fostering higher-order cognitive skills. To bridge this gap, an instructional model emphasizing the development of higher-order thinking was designed. This model incorporates active learning, problem-solving, collaboration, scaffolding, reflection, and self-monitoring, organized into six steps: prior knowledge activation, mediation, internalization, generalization, transfer, and evaluation. The model was evaluated using a 5-point Likert scale, achieving a mean score of 4.33 (SD = 0.70), indicating high levels of appropriateness and acceptability. Furthermore, a pilot test yielded an effective index (E.I. = 0.51), demonstrating the model's efficacy in fostering metacognitive and problem-solving skills.